Pope Gregory IX (1227-1241)
1 online resource.
Keywords: As Cardinal Hugo and as pope, Gregory was one of the dominant figures in the history of the papacy of the High Middle Ages. Coming to prominence under Pope Innocent III, Hugo played an important political role, particularly as legate on various occasions, as well as being a major promoter of the new religious orders. As pope, his battle with Emperor Frederick II is one of medieval history's most absorbing conflicts. But he also acted as peacemaker, promoter of the Crusades, instigator of mission for the sake of conversion, refomer of the Curia, patron of arts and liturgy, and as a passionate advocate of Church reform. His decretal collection, the Liber Extra, was the most influential of the Middle Ages. A full examination of Gregory's pontificate is very long overdue. The current volume brings together a team of international scholars, each of them expert in dealing with a particular aspect of the pontificate, and provides what will be a collection of studies of lasting scholarly value on a central figure of the medieval papacy.